(3QSGdI aj GdeaGQbGJs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje GdeaGQbGJ CQHY eQGJH eNJdaI GdMbGFb GdeQJHI GdChdi GdehLhO GdPi dGSHH dg hgh hGMO GdKGfjI GdYbhd GdaYGdg s
(3BNQgG (B:s
(3hcKjQ ef GdGhSGW dcGfJ GdfaS TF hGMO YGdeI hMGedI ebGe s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3eUOQ GbJfGA GdCUd (B:s
(3EjQGf s
Keywords: (3GdadSaI hGdefWbs